Gait characteristics in idiopathic normal pressure hydrocephalus: a review on the effects of CSF tap test and shunt surgery - Iva Hereitová; Alessandra Griffa; Gilles Allali; Tomáš Dorňák (European Journal of Medical Research)
Abstract Background Idiopathic normal pressure hydrocephalus (iNPH) is a progressive disease characterized by disproportionate ventricular enlargement at brain imaging with gait disturbance and an increased risk of falling. Gait assessment is a key feature in the diagnosis of iNPH and characterization of post-surgical outcomes. Research question How do gait parameters change 24 h after CSF tap test (CSFTT) and after ventriculoperitoneal shunt surgery? Methods The PRISMA guidelines were used to perform the systematic review. We conducted a search of the following electronic databases: PubMed, Medline, Web of Science and EBSCO. We included studies focusing on gait changes occurring 24 h after a CSFTT or after ventriculoperitoneal shunt surgery in patients with iNPH. All articles were assessed for methodological quality using an adapted version of The Standard Quality Assessment Criteria for Evaluating Primary Research Papers checklist. Results Twenty-seven studies were included in the systematic review. Studies were highly heterogeneous due to lack of standardization of CSFTT or shunt surgery methodology, with varying amounts of CSF removed during the tap test (20–50 ml) and varying time of outcome assessment after shunt surgery. Dynamic equilibrium measurements are generally used to assess preoperative levels of cardinal symptoms and postoperative outcomes in iNPH. The most sensitive spatio-temporal parameter assessed 24 h after CSFTT was self-selected walking speed followed by stride length, which increased significantly. Cadence is hence not suitable to consider in the evaluation of effect of CSFTT and shunt surgery. Changes in balance-related gait parameters after CSFTT and shunt surgery are still a controversial area of research. Conclusion Gait assessment is a key feature in the diagnosis of iNPH and characterization of post-surgical outcomes. Dynamic equilibrium measurements are generally used to assess preoperative levels of cardinal symptoms and postoperative outcomes in iNPH, but quantitative and standardized gait analysis procedures are missing. Changes in balance-related gait parameters after CSFTT might be useful in deciding whether to perform shunt surgery in iNPH patients who hope for improvement in gait ability. The dual-task paradigm after CSFTT could improve the clinical evaluation of higher level frontal gait disturbances in patients with suspected iNPH before shunting.